(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
This investigation comes up due to several questionings on the punishible act of risk exposition in land transit: on one hand, there is the permanent question on the possible double penalty for one manner, since once the blood-alcohol limit for penal relevance has been reached, the people can likewise be penalized in administrative courts; as well as the increased number of cases considered as “minor”, on account of the low foreseen penalty they hold, which in turn join an overloaded judiciary system, that is currently colapsed by the amount of open case files. And on the other hand, it cannot be ignored that, in spite of the efforts made by authorities, the number of victims with permanent and serious injuries, or even deads, as a result of accidents involving alcohol or drug use, remains rising. All these facts cause the State both concern and burden, understood by the impact these casualties have on the gross domestic product, and on the budgets of serveral Ministries and public institutions. For such reasons, it can be affirmed that it still exists many vacuums over which it is necessary and urgent to ignite debate. Part of the research was made during the stay in the cities of Alcalá de Henares and Madrid – Spain, within the framework of an exchange and investigation programme, financed by CONACYT.